QUALITY OF LIFE ANALYSIS AMONG ELDERLY PATIENTS USING REMOVABLE PARTIAL DENTURES - Wardhana, Erdianto Setya; Rizky, Novi Sagita; Styaningrum, Yunita; Ratnawati, Irma Dewi; Naimaturrohmah, Army (Indonesian Journal of Dentistry, 2025)
Background: The elderlies are prone to the process of the gradual decreasing ability of the tissue for self-healing. This process greatly affects the dental structure and periodontal tissue leading to tooth decay. When it is not properly treated, it may disturb oral functions and activities influencing their life quality.Aim & Objectives: This research, therefore, aims to obtain the description of quality of life on elderly patients with removable denture at Prosthodontic Installation of Islmic Dental Hospital (RSIGM) Sultan Agung Semarang indonesia.Methods : Research was conducted with a descriptive method using the consecutive technique sampling method. Data were collected from 31 elderly patients with removable denture at the Prosthodontic Islmic Dental Hospital (RSIGM) Sultan Agung Semarang indonesia and quality of life was measured by Geriatric Oral Health Assesment Index (GOHAI) questionnaire. The assessment criteria were that if the score was 0.0–1.67, it meant the quality of life was poor; a score of 1.67–2.3 meant the quality of life was moderate; and a score of 2.4–3 meant the quality of life was good.Results: The results showed that the dimensions of physical function fell into the moderate criteria (2,25), while the dimensions of pain and inconvenience (2,55) and psychosocial aspects were considered good (2,50).Conclusion: It can be concluded that the general quality of life on elderly patients with removable denture at the Prosthodontic Clinic RSIGM Sultan Agung  were good